Isolation and Phenotypic Characterization of Multidrug-Resistant Pseudomonas aeruginosa Isolated from Wounds and Burns of Patients in an Iraqi Clinical Setting: A Study of Their Distribution and Antibiotic Resistance - Kadhem Dahil Alburki , Ziyad; Gjir Jremich, Samira ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Infections from Pseudomonas aeruginosa represent a significant public health threat as a result of the organism’s innate and acquired resistance to a wide breadth of antimicrobial agents. The aim of study was to isolate and phenotypic characterization of multidrug-resistant Pseudomonas aeruginosa isolated from wounds and burns of patients in an Iraqi clinical setting. A combined total of 100 clinical samples were collected, evenly distributed between wound (n = 50) and burn (n = 50) specimens. Sterile swabs were used to collect the samples directly from the infection sites. Upon collection, the swabs were placed into transport tubes before transferring the samples in tubes to the laboratory, to maintain sample integrity and ensure optimal recovery conditions for bacterial isolation. The results showed that Pseudomonas aeruginosa was isolated from 30 of the 100 clinical samples (30%) and significant differences were found between burn samples (36%) and wound samples (25%) but this was not statistically significant (X² = 1.714, P = 0.19). The isolates showed distinctive characteristics on Cetrimide and King’s a media, which produced Pyoverdin and Pyocyanin pigments (respectively). The result for both oxidase and catalase tests were both positive confirming the identity of the isolates as Pseudomonas aeruginosa. Patients aged 50 or older had higher isolation rates for both genders. However, the testing statistic showed that there was no relationship between age or gender and isolation rate (P > 0.05). DOI: https://doi.org/10.54633/2333-024-056-004